2017
DOI: 10.1039/c6ay02921c
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of kasugamycin and validamycin-A in fruits and vegetables using liquid chromatography-tandem mass spectrometry and consecutive solid-phase extraction

Abstract: A method based on a ReproSil 100 C18 column without any ion pairs or buffer additives is proposed for the determination of polar aminoglycosides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Nevertheless, it was reported that the retention time and sensitivity were excellent, and because of confirming this, sufficient retention time and sensitivity were secured, as shown in Fig. 1(c) [7,10,19]. Therefore, in this study, an amide column highly effective for kasugamycin was selected and analyzed.…”
Section: Establishment Of Lc/ms/ms Analysis Conditionssupporting
confidence: 52%
See 2 more Smart Citations
“…Nevertheless, it was reported that the retention time and sensitivity were excellent, and because of confirming this, sufficient retention time and sensitivity were secured, as shown in Fig. 1(c) [7,10,19]. Therefore, in this study, an amide column highly effective for kasugamycin was selected and analyzed.…”
Section: Establishment Of Lc/ms/ms Analysis Conditionssupporting
confidence: 52%
“…Therefore, in this study, water and acetonitrile, commonly used to analyze aminoglycoside antibiotics, were selected as the mobile phase solvent, and 0.1% formic acid solution was added to improve the sensitivity and resolution efficiency of the target component [5,18]. Previous studies found that the sensitivity of the analyte is increased when a 0.1% formic acid solution is added to the mobile phase, while the sensitivity of the signal decreases when a concentration lower than 0.1% is added [8,19].…”
Section: Establishment Of Lc/ms/ms Analysis Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, chromatographic based technology is the mainstream of antibiotic detection, especially high-performance liquid chromatography (HPLC). [11][12][13] Although the sensitivity and accuracy of separation technology based are excellent, the disadvantages such as complicated operations and pretreatment procedures are unavoidable.…”
Section: Introductionmentioning
confidence: 99%
“…Micropollutants such as heavy metal ions and antibiotic residues are currently studied using solid-liquid extraction, liquid-liquid extraction, and liquid membrane extraction, based on adsorption and extraction fundamentals [12][13][14][15], followed by analytical techniques, such as inductively coupled plasma-mass spectrometry (ICP-MS), mass spectrometry (MS), atomic absorption spectrometry (AAS)-electrothermal, graphite furnace-X-ray fluorescence spectroscopy (R-FS) [16][17][18], liquid chromatography-mass spectrometry (LC-MS), and high-performance liquid chromatography (HPLC) [19][20][21]. These methods are complicated, time-consuming, and expensive and require trained personnel and extensive sample preparation and purification prior to analysis [22,23].…”
Section: Overviewmentioning
confidence: 99%